Analisis Perencanaan dan Pengendalian Obat di Rumah Sakit Pluit Tahun 2015 - Endang Setiawati; Anny Victor Purba; Wahyudi Uun Hidayat (JURNAL ILMU KEFARMASIAN INDONESIA, 2020)
Drug planning at Pluit Hospital is carried out using a consumption method that is based on previous use. The purpose of this study was to determine the investment value and use of drug supplies based on a combination of consumption methods with ABC, VEN and Reorder Point (ROP) analysis. This research is a qualitative and quantitative descriptive study with retrospective data collection during the period May-October 2016 at Pluit Hospital. ABC analysis results based on the investment value of the total group A drug items have a percentage of 69.90%; group B 20.07% and group C 10.03%. ABC analysis results based on the use of group A 69.95%; group B 20.04% and group C 10.01%. VEN analysis results for group V 3.24% absorbed investment of 5.15%; group E 60.10% absorbed investment 76.56% and group N 36.66% absorbed investment 18.29%. Analysis of drug planning based on ABC and VEN methods has high, medium and low investment values, usage values ​​and NIK. While the analysis of drug control based on the method of Lead Time, Safety stock and Reorder Point guarantees the availability of drugs on an ongoing basis.